If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2/3(6x+1)-x=8
We move all terms to the left:
2/3(6x+1)-x-(8)=0
Domain of the equation: 3(6x+1)!=0We add all the numbers together, and all the variables
x∈R
-1x+2/3(6x+1)-8=0
We multiply all the terms by the denominator
-1x*3(6x+1)-8*3(6x+1)+2=0
Wy multiply elements
-3x^2(6-24x(6+2=0
| 3x-24+45=45 | | (3x+11)/4=11 | | -3x+2=12x-47 | | 2x+7x=85+2 | | ?x10=40 | | 33(11+x)=21-1+x | | -20t=20-19t | | -2=-2j | | 10x+6+6x+30=180 | | 8y+17=-50.8 | | -6(n+2)=-3-33 | | (2x-5)/5=3 | | 7y+4=3y+4 | | 3x+5=4x-60 | | 2x-0.4=3.6 | | 32=5x-7 | | 6-8s=-9s | | x²=⅘ | | 2b-1=1+4 | | 4(2x-5)=6x-12 | | -x-7=32 | | 5(4-2w)-8=-8 | | -20f-20-3f=-19f+20 | | x+7/12=9 | | 120-4x=180-8x | | 5/3=y+3/7 | | 8-12x=32* | | 4=4x/9 | | 7/2=6/b-4 | | 8x=(x-7) | | x-0,5=2,5 | | x²=⅖ |